Socio-demographic factors of allergy awareness among pre-university student in Selangor - Tengku Azhar, Tengku Norbaya; Mohamed, Malissa; Abdul Ghani, Radiah (Universiti Malaysia Pahang, 2019)
Allergic disease is a worldwide public health issues and substantially growing over the past 20 years. Due to drastically changes of environmental and dietary culture within the population, Malaysia as one of the developing country is no exception to face the same problem. This study aimed to assess the awareness of allergy diseases and its prevalence using cross-sectional survey method. This study that has been conducted to 138 students from University Teknologi Mara Cawangan Dengkil, Selangor, Malaysia. A self-administered questionnaire was used as an instrument for data collection. Based on sociodemographic data, the mean of knowledge between science and non-science students showed the significant difference. Respondents from Science course score significantly higher for part B (4.54 ± 1.654) compare with other courses. The outcome of the study also showed that, among 138 respondents, n=80 (58%) of them perceived themselves to suffer allergy diseases and it symptoms. Common food to cause food allergy in this study were identified as seafood with n=43 (31.25%) followed with dust with n=40 (29%), peanuts with n=14 (10.1%). The study also indicated the intricate situation of cross reactivity as n=21(15.2%), n=6 (4.3%) and n=1(0.7) of respondents suffered with two, three and four multi allergy reaction respectively. The factor such as family history which subjected to predisposition of genetic factor was strongly associated with occurrence of allergic among respondents. It determined from Chi Square Test (X²) that showed that, there is high significant association (P<0.001) between parental allergies with respondents allergies. As overall, it can be conclude that the knowledge of allergy term, cause and prevention were relatively low among population under study as compared to the previous study.